Association of Physical Activity Levels with Cardiometabolic Risk Factors in a Sample of Iraqi Adults (Iraqi Journal of Medical Sciences, 2024)
Background: Physical activity is a crucial determinant of cardiovascular health and metabolic well-being.Objective: To investigate the association between physical activity levels and various cardiometabolic risk factors in a sample of adults. Methods: A cross-sectional study was conducted on 140 adults, with complete data available for analysis. The participants' physical activity levels were categorized as high or low. Several cardiometabolic risk factors, including age, sex, smoking status, alcohol consumption, food style, body mass index (BMI), blood pressure, glycated hemoglobin, cholesterol levels, triglycerides, high-density lipoprotein, low-density lipoprotein, very-low-density lipoprotein, waist circumference and uroguanylin (UGN) were assessed. Chi-square tests and t-tests were conducted to examine the significance of associations between physical activity levels and each risk factor.Results: The study found that physical activity levels were significantly associated with younger age (P
Keywords: Physical activity; cardiometabolic risk factors; adults; BMI; cholesterol; triglycerides; HDL; LDL; VLDL; HbA1c; Uroguanylin